The Principal's Strategy in Marketing Educational Services at the Integrated Islamic Vocational High School (SMK IT) Abi Husni Meranti - Sonia Purba Tambak; Yusuf Hadijaya; Inom Nasution (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to analyze and explain the principal's strategy in marketing educational services at Abi Husni Meranti IT Vocational School, which includes formulation, implementation, evaluation of strategies, as well as the obstacles faced and how to overcome them. The research took place from March to May 2024, with initial observations in December 2023. The method used was qualitative research with a case study approach with narrative characteristics. Researchers go directly into the field to obtain data through observation, interviews and recording. This approach allows researchers to investigate phenomena intensively and in depth. The research results show that strategy formulation is carried out through marketing planning, market identification, strategy creation, and strategy control. Strategy implementation involves market segmentation, marketing mix, school services, relationship marketing, and consistency in implementation. Strategy evaluation includes a review of internal and external factors, performance reviews, and continuous improvement and improvement. The obstacles faced include teacher discipline, the burden of activities on students, and the community's low mindset regarding education. To overcome these obstacles, the principal reprimands teachers personally, takes a personal approach to students, and consistently implements the planned program.